Imperforate Anus with Fistula Exiting at the Penile Skin - Sfoungaris, Dimitrios (J Clin Diagn Res, 2016)
We present the case of a male neonate with imperforate anus and a fistula exiting on the penile skin. Anorectal malformations in boys often present themselves with an entero-perineal or entero-urinary tract fistula, the type of which is a key feature for the classification and the treatment plan. A fistula exiting in front of the scrotum, such as described in our case, is very rare and is not incorporated in the current classification and treatment algorithms. Scarce reports on misjudgment concerning the position of the blind rectal pouch in similar cases, led us to perform a colostomy instead of a one-stage correction. A posterior sagittal anorectoplasty was performed eight months later and the rectal pouch was found inside the levator sling, justifying the cautious approach. The colostomy was closed three months later and after six months the distal part of the fistula was excised. We believe that in cases with a rare fistula presentation, the position of the rectal pouch is not predictable and the surgeon should proceed with caution.